Five-Year Survival of Short Single-Tooth Implants (6 mm): A Randomized Controlled Clinical Trial. (July 2018) - Naenni, N.; Sahrmann, P.; Schmidlin, P.R.; Attin, T.; Wiedemeier, D.B.; Sapata, V.; Hämmerle, C.H.F.; Jung, R.E.
The aim of the present study was to evaluate whether 6-mm dental implants in the posterior segments of either jaw perform equally well in terms of clinical and radiographic outcomes when compared with 10-mm implants after 5 y of loading. Patients with single-tooth gaps in the posterior area who were scheduled for implant therapy were randomly assigned to a group receiving either a 6- or 10-mm implant. After a healing period of 10 wk, implants were loaded with a screw-retained single crown and followed up at yearly intervals. Of 96 patients, 86 could be recalled after 5 y. The implant survival rates amounted to 91% (95% confidence interval: 0.836 to 0.998) for the 6-mm group and 100% for the 10-mm group ( P = 0.036). Median crown-to-implant (C/I) ratios were 1.75 (interquartile range [IQR], 1.50 to 1.90) for the 6-mm group and 1.04 (IQR, 0.95 to 1.15) for the 10-mm group, whereas the median marginal bone levels measured −0.29 mm (IQR, −0.92 to 0.23) for the 6-mm group and −0.15 mm (IQR: −0.93 – 0.41) for the 10-mm group after 5 y. The C/I ratio turned out to be statistically significant ( P < 0.001), whereas marginal bone levels showed no significant difference between the groups. The 6-mm implants exhibited significantly lower survival rates than the 10-mm implants over 5 y, whereas there was no difference between upper and lower jaws in terms of survival ( P = 0.58). Lost implants did not show any sign of marginal bone loss or peri-implant infection previous to loss of osseointegration. High C/I ratio and implant length had no significant effect on marginal bone level changes or technical and biological complications (German Clinical Trials Registry: DRKS00006290).